Effect of bleaching agents on discoloured resin-based composites for direct restorations: A systematic review - Khaled Abid Althaqafi; Abdulrahman Alshabib (Wolters Kluwer Medknow Publications, 2023)
The purpose of the review was to assess the influence of office and home bleaching on the color durability after staining of resin-based composites (RCs) for direct restorations. A web-based search for possibly relevant scientific papers in the English language between January 2013 and August 2022 was conducted in the databases such as PubMed, Scopus, Cochrane Library, and EMBASE. In-vitro studies that explored the influence of in-office and other bleaching treatments on the discolored RC for direct restorations in extracted human teeth were included. Case studies, case series, animal studies, systematic reviews, and letters to the editor were not considered. A total of 212 articles from a web-based search and 32 studies from a manual search were retrieved. After removal of duplicate records, 181 titles and abstracts were reviewed for eligibility; 92 were chosen for full-text analysis, and nine in-vitro studies matched the inclusion criteria. The two examiners examined the methodological quality of the selected studies independently based on the study design, methodological soundness, and data analysis. Distinct values were assigned to studies evaluating color variations of stained RC subjected to bleaching agents. The methodological quality scores were expressed as a percentage of the highest possible score based on the established scoring system and categorized as indicating a low, moderate, and high level of evidence. The reversal of color alterations following home and office bleaching was found to be dependent on the RC used. Within the limitations of the in-vitro investigations, it was deduced that the bleaching agents were successful in eliminating stains and improving the durability of the color to near baseline values.